Boosting Students’ Speaking skill using Ted Talks YouTube Videos: Teacher Talk Theory - Imroatul Karimah; Slamet Setiawan; Ahmad Munir (Yayasan Visi Intan Permata, 2022)
Even though the importance of teaching English speaking using TED Talks to improve students’ speaking skill has been acknowledged, however, far too little attention has been paid to investigate students’ perceptions on the use of TED Talks dealing with teacher talk categories such as dealing with feelings, praising and encouraging, making joke, as well as giving direction and lecturing. This study aimed to investigate the concordance of the students’ speech ability development and the students’ interest and motivation towards the use of TED Talks to boost the students’ speaking skill. This present used both quantitative and qualitative design. The samples of the students were 27 students from grade 7E in MTsN Surabaya. For the quantitative data, the data was collected using pre-test and post-test. However, for the qualitative data, the data was gathered using interview protocol. The data was analyzed using descriptive analysis. The findings of this study found that the students improve their English speaking skill especially the pronunciation and the fluency of delivering English speech in front of their friends after the treatment using the TED Talks videos. Regarding the students’ perceptions of the use TED Talks to support teacher talks, most of the students agreed that TED Talks videos can support teacher talks related to the category of dealing with feelings, praising and encouraging, making jokes and giving direction as well as lecturing.